Klasifikasi Tanah Berdasarkan Taksonomi Tanah 2014 di Desa Sembahe Kecamatan Sibolangit - Frisca Panjaitan; Jamila Jamilah; M. M. B. Damanik (Jurnal Agroekoteknologi, 2015)
Sembahe is believed to have a great potential particularly in agricultural sector. In order to discover this potent it is necessary to classify the soilfirst by using USDA Soil Taxonomy 2014th edition which has not been done before. This research conducted in between December 2013 and February 2014. The soil profiles was made from two representative location. The first is located at 03020’40” S 98035’30” E, with altitude 231 meter above mean sea level. Meanwhile the second is located at 03020’42” S 98035’05” E withaltitude 294 meter above mean sea level. Morphological properties identified by describing the soil profiles using manual book while physical and chemical properties identified at laboratory. Soil samples was taken from each horizon at every profiles and analyzed for particle size distribution, bulk density, organic carbon, exchangeable cations (Ca2+, Mg2+, K+, and Na+), pH in a 1:2 soil:water ratio, pH in KCl solution, phosphate retention, and also kation exchange capacity (CEC).The results show that the soil in Sembahe Village at profile I classified as Inceptisols Order, Udepts Sub Order,Humudepts Great Group, and Cumulic Humudepts Sub Group, andat profile II classified as Inceptisols Order, Udepts Sub Order, Dystrudepts Great Group, and Typic Dystrudepts Sub Group.Keywords : Soil Classification, Soil Taxonomy 2014, Inceptisols